1999
DOI: 10.1021/ie9807001
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Computational Issues in Stochastic Design and Planning Optimization Problems

Abstract: In stochastic process design and planning optimization problems, the expected value of the objective function in face of uncertainty is typically evaluated through an n-dimensional integral, where n is the number of uncertain parameters. In this paper, suitable integration techniques are presented and computational issues are discussed in relation to the number of uncertain parameters and the uncertainty model considered. A specialized cubature technique, suitable to integrate normally distributed uncertaintie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…The number of simulations, that are performed sampling the uncertain parameters according to the above-described quasi-Monte Carlo technique, is increased until the results converge to 10 -1 . It is found that 1000 simulations are required, which is in agreement with results reported by Bernardo et al (1999). Overall, the simulations require computation time on the order of several hours.…”
Section: Setting Up Simulation For Relaxation-based Dependability Anasupporting
confidence: 87%
See 3 more Smart Citations
“…The number of simulations, that are performed sampling the uncertain parameters according to the above-described quasi-Monte Carlo technique, is increased until the results converge to 10 -1 . It is found that 1000 simulations are required, which is in agreement with results reported by Bernardo et al (1999). Overall, the simulations require computation time on the order of several hours.…”
Section: Setting Up Simulation For Relaxation-based Dependability Anasupporting
confidence: 87%
“…In contrast to the random selection, a deterministic sequence of points can ensure that the most representative sample of the parameter space is obtained. It has been pointed out in the literature that these sampling methods only need to visit a small fraction of the space to obtain a representative answer (Bernardo et al, 1999). As Monte Carlo methods are often applied to problems where each function evaluation at a sample point is computationally expensive, as is the case in the problem studied here, simulations only on the order of hundreds to thousands can be performed in reasonable time.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature varies on the choice of risk measure, and how the decision-maker's preferences are taken into account. The prices in each scenario are independent by definition, but within each scenario the product prices are conspicuously correlated with each other, and not independent as stated for example in Bernardo et al (1999). Therefore, the prices are considered constant, and the amounts that go into each product as the random variables.…”
Section: Objective Function For the Refinery Including Stochastic Pricesmentioning
confidence: 99%